Биомеханика ударных движений; ХХI Съезд Физиологического общества им. И. П. Павлова, Калуга, 19-25 сентября 2010 г. - Бредихина Ю. П. Юлия Петровна; Гужов Ф. И. т. е. [Ф. А.]; Капилевич Л. В. Леонид Владимирович; Андреев В. И. Владимир Игоревич (2010, 2010)
Заглавие с экрана